2022
DOI: 10.3389/fendo.2022.1001985
|View full text |Cite
|
Sign up to set email alerts
|

Is there a secular trend regarding puberty in children with down syndrome?

Abstract: IntroductionThere are very few studies on the age of onset and end of puberty in children with Down syndrome (DS). Also, data regarding the course of puberty in these children compared to their healthy peers is limited. Moreover, there is limited information regarding the effects of factors such as obesity and hypothyroidism on the puberty process in children with DS. Our aim in our study is to determine whether the pubertal development of children with DS differs from their healthy peers and from previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…These data apparently differ from those drawn by more recent studies. For example, in a cohort of children with DS, Erdoğan and colleagues reported pubertal onset at a median age of 10.0 years for both genders, which is superimposable with the outcomes more recently described for age-matched peers ( 58 ). In addition, the average age of menarche in adolescents with DS is consistent with the general population in several study cohorts ( 58 60 ).…”
Section: Puberty and Gonadal Functionsupporting
confidence: 54%
See 2 more Smart Citations
“…These data apparently differ from those drawn by more recent studies. For example, in a cohort of children with DS, Erdoğan and colleagues reported pubertal onset at a median age of 10.0 years for both genders, which is superimposable with the outcomes more recently described for age-matched peers ( 58 ). In addition, the average age of menarche in adolescents with DS is consistent with the general population in several study cohorts ( 58 60 ).…”
Section: Puberty and Gonadal Functionsupporting
confidence: 54%
“…For example, in a cohort of children with DS, Erdoğan and colleagues reported pubertal onset at a median age of 10.0 years for both genders, which is superimposable with the outcomes more recently described for age-matched peers ( 58 ). In addition, the average age of menarche in adolescents with DS is consistent with the general population in several study cohorts ( 58 60 ). Overall, the difference in the timing of pubertal attainment reported by different authors likely mirrors most of the changes experienced by the general pediatric population over the last decades.…”
Section: Puberty and Gonadal Functionsupporting
confidence: 54%
See 1 more Smart Citation
“…This was only seen for the males in the 9–18 years age group for hip flexion and elbow flexion and extension. It is unclear if this could indicate a difference in puberty for females with DS, and it has been suggested that puberty onset and course may be different in females with DS compared to healthy neurotypical children (Erdogan & Guven, 2022). Additionally, children with DS are at increased risk for endocrine disorders such as short stature, obesity, and hypothyroidism (Cebeci et al, 2013; Rubin et al, 1998), which can also impact joint ROM and could contribute to decreased joint ROM seen in the female groups.…”
Section: Discussionmentioning
confidence: 99%